2019
DOI: 10.1007/s10071-019-01275-0
|View full text |Cite
|
Sign up to set email alerts
|

Innovative problem solving in great apes: the role of visual feedback in the floating peanut task

Abstract: Nonhuman great apes show remarkable behavioural flexibility. Some individuals are even able to use water as a tool: They spit water into a vertical tube to make a peanut float upwards until it comes into reach (floating peanut task; FPT). In the current study, we used the FPT to investigate how visual feedback, an end-state demonstration and a social demonstration affect task performance in nonhuman great apes in three experiments. Our results indicate that apes who had acquired the solution with a clear tube … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
20
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(25 citation statements)
references
References 53 publications
3
20
1
Order By: Relevance
“…However, researchers have also investigated several more specific topics with sanctuary-housed chimpanzees, such as the influence of both social presence [164] and early rearing history [165] on problem-solving. Other problemsolving research has looked at chimpanzees' use of causal and arbitrary cues [166] as well as the role of visual feedback in the floating peanut task [167]. The performance of chimpanzees at Ngamba on the floating peanut task has also been studied comparatively with human children and nonsanctuary-housed gorillas (Gorilla gorilla gorilla) and orangutans (Pongo pygmaeus) [168].…”
Section: (B) Cognitionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, researchers have also investigated several more specific topics with sanctuary-housed chimpanzees, such as the influence of both social presence [164] and early rearing history [165] on problem-solving. Other problemsolving research has looked at chimpanzees' use of causal and arbitrary cues [166] as well as the role of visual feedback in the floating peanut task [167]. The performance of chimpanzees at Ngamba on the floating peanut task has also been studied comparatively with human children and nonsanctuary-housed gorillas (Gorilla gorilla gorilla) and orangutans (Pongo pygmaeus) [168].…”
Section: (B) Cognitionmentioning
confidence: 99%
“…As in other settings, the methods to study cognition in sanctuaries are highly varied, ranging from puzzles [129,138,167,168] to video playbacks of conspecifics [181]. Among the most common studies, in both range-and non-royalsocietypublishing.org/journal/rsbl Biol.…”
Section: (B) Cognitionmentioning
confidence: 99%
“…Tennie et al (2010) concluded that the observational learning, specifically emulation, increased the success of the chimpanzees. Ebel et al (2019) found that none of the 24 sanctuary-living chimpanzees in Experiment 1 solved the task with an opaque tube, although one chimpanzee solved the task after viewing a water-filled tube with a peanut floating on top (end-state condition). In Experiment 2, five out of 18 zoo-living chimpanzees (28%, 13 of 18 had failed to solve the task in a previous study) and none of the six bonobos they tested solved the floating object task (Ebel et al, 2019).…”
mentioning
confidence: 96%
“…Ebel et al (2019) found that none of the 24 sanctuary-living chimpanzees in Experiment 1 solved the task with an opaque tube, although one chimpanzee solved the task after viewing a water-filled tube with a peanut floating on top (end-state condition). In Experiment 2, five out of 18 zoo-living chimpanzees (28%, 13 of 18 had failed to solve the task in a previous study) and none of the six bonobos they tested solved the floating object task (Ebel et al, 2019). In Experiment 3, six of eight chimpanzees and four of five Sumatran orangutans that previously succeeded on the task solved it in a re-test (Ebel et al, 2019).…”
mentioning
confidence: 96%
See 1 more Smart Citation